Question: Prove the following trigonometric identity: \dfrac{cosA}{cosA -sinA} - \dfrac{cosA}{cosA +sinA} = tan2A


Solution:

LHS
= \dfrac{cosA}{cosA -sinA} - \dfrac{cosA}{cosA +sinA}

= \dfrac{cosA(cosA +sinA) -cosA(cosA -sinA}{(cosA -sinA)(cosA +sinA)}

= \dfrac{cosA (cosA +sinA -cosA +sinA}{cos²A -sin²A}

= \dfrac{cosA(2sinA)}{cos 2A}

= \dfrac{2sinAcosA}{cos 2A}

= \dfrac{sin 2A}{cos 2A}

= tan 2A
RHS

Related Notes And Solutions:

Link: Introduction To Trigonometry
Link: Values of Trigonometric Ratios
Link: Compound Angles

#SciPiPupil